Training in the process of insertion into teaching in the centers of the Society of Jesus: A competency approach (Journal of Parents and Teachers, 2023)
Initial teacher training today is a highly complex challenge that requires different strategies and tools. In this article, a basic competency framework for Ignatian teachers is presented, specifying ten basic competencies. From this competency approach, we reflect on the approaches that should characterize teacher training in this initial stage and identify some specific instruments and methodologies that can serve the effective development of these competencies.
Keywords: teacher training; teaching competencies; Society of Jesus; teacher professional development; Ignatian pedagogy